Chemical composition of essential oil from Petroselinum crispum (Mill) Nyman ex A.W. Hill "parsley" and determination its antibacterial activity - Vivanco T, Reider (2012)
The study aimed to analyze the chemical composition of the essential oil from leaves of Petroselinum crispum (Mill) Nyman ex A.W. Hill "perejil" and determine antibacterial activity. Essential oil was obtained treating 20 kg of fresh leaves with a distillation equipment by dragging with steam; obtaining performance of 0,02 per cent and four milliliters of oil v/p. In the qualitative analysis was analyzed its solubility in organic solvents, and chemical components were determined by gas chromatography / mass spectrometry (GC/MS), achieving the elucidation of the following compounds: 1R-α-pinene, β-pinene, β-phellandrene, p,α-dimethyl estirene, (E)-2-caren-4-ol, 1,3-benzodioxol-(2-propenil) 4-metoxy-6, 1,3-benzodioxol, 4,7-dimetoxy-5-(2-propenil)-. In vitro bacterial activity determination was made by the method of diffusion in agar, demonstrating significant activity to Staphylococcus aureus ATCC 25933 and Staphylococcus epidermidis clinical strain to concentrations of 100 and 50 per cent; for Pseudomonas aeruginosa ATCC 2783 to 100 per cent concentration, having little to no activity against Bacillus subtilis and Escherichia coli. The results showed that the chemical composition of the essential oil of Petroselinum crispum (Mill) Nyman ex A.W. Hill "Parsley" presented antibacterial activity. Keywords: Petroselinum crispum “perejil”, essential oil, antibacterial activity.